Identification and characterization of novel microRNAs in disease-resistant and disease-susceptible Penaeus monodon. Issue 119 (December 2021) - Mondal, Debabrata; Chakrabarty, Usri; Dutta, Sourav; Mallik, Ajoy; Mandal, Nripendranath
Abstract: MicroRNAs (miRNAs), known as a translational regulator, are evolutionary conserved, small, and noncoding RNA. They have played a vital role in disease biology through the host-virus-miRNA-interaction. In this study, novel miRNAs of naturally occurring, virus-free disease-resistant and disease-susceptible Penaeus monodon were identified and characterized. In disease-susceptible samples, 45 homologous mature miRNAs and 28 homologous precursor miRNAs were identified. In disease-resistant samples, 52 homologous mature miRNAs and 87 homologous precursor miRNAs were identified. In disease-susceptible samples, 33 novel mature miRNAs and 33 novel precursor miRNAs were identified. In disease-resistant samples, 523 novel mature miRNAs and 141 novel precursor miRNAs were identified. Differential expression study revealed the up-regulated and down-regulated miRNAs in disease-resistant and disease-susceptible P. monodon . Gene ontology pathway of known and novel miRNAs revealed that P. monodon miRNAs might have a potential and specific role in signal transduction, cell-to-cell signaling, innate immune response and defense response to different pathogens. Highlights: In Penaeus monodon, homologous 78 mature and 94 precursor miRNAs were identified. In P. monodon, novel 556 mature and 174 precursor miRNAs were identified. First identification of homologous and novel miRNAs from virus free P. monodon. Known and novel miRNAs might have a crucial role in innate immunity in P. monodon. Differential expression study revealed the up-regulation of top 65 known miRNAs.